2012
DOI: 10.1007/s10548-012-0248-8
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Fitness and the Brain: Increased N-Acetyl-Aspartate and Choline Concentrations in Endurance-Trained Middle-Aged Adults

Abstract: Engagement in regular aerobic exercise is associated with cognitive benefits, but information on the mechanisms governing these changes in humans is limited. The goal of the current study was to compare neurometabolite concentrations relating to cellular metabolism, structure, and viability in endurance-trained and sedentary middle-aged adults. Twenty-eight endurance-trained and 27 sedentary adults, aged 40–65 years, underwent general health assessment, cardiorespiratory fitness measurement, neuropsychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 52 publications
3
48
1
Order By: Relevance
“…This training-induced alteration in metabolic profile was also found in a previous study in humans where they detected acutely increased Glx (combined glutamate and glutamine signal) in the visual cortex after 10 min of vigorous exercise (Maddock, Casazza et al 2011). Other studies in humans used MRS to deduce metabolic changes resulting from endurance-training in middle-aged subjects (Gonzales, Tarumi et al 2013), fast GABA level alterations were observed in the sensorimotor cortex due to motor-learning preclinical research involving animal models can be translated to the human brain (Nithianantharajah andHannan 2006, Svensson, Lexell et al 2014). A particularly interesting preclinical example can be found in a (preliminary) study by Little et al (2012).…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…This training-induced alteration in metabolic profile was also found in a previous study in humans where they detected acutely increased Glx (combined glutamate and glutamine signal) in the visual cortex after 10 min of vigorous exercise (Maddock, Casazza et al 2011). Other studies in humans used MRS to deduce metabolic changes resulting from endurance-training in middle-aged subjects (Gonzales, Tarumi et al 2013), fast GABA level alterations were observed in the sensorimotor cortex due to motor-learning preclinical research involving animal models can be translated to the human brain (Nithianantharajah andHannan 2006, Svensson, Lexell et al 2014). A particularly interesting preclinical example can be found in a (preliminary) study by Little et al (2012).…”
Section: Accepted Manuscriptsupporting
confidence: 79%
“…However, this age–fitness interaction may be regionally specific. Another research group found greater NAA in a similar sized anterior cingulate region of interest in fitter middle-aged adults (age 40–65 years) compared with their less-fit peers [197]. A limitation of this method is evident in these two studies; it is currently not possible to perform a whole-brain MRS scan, which compromises comparability across studies and across participants in longitudinal assessment.…”
Section: Neurogenesis and Brain Structurementioning
confidence: 99%
“…Exercise training has also been shown not only to influence physical fitness positively, but also cognition (Kramer and Erickson 2007a, b). Its effects are positive for both normal and cognitively impaired adults, middle-aged adults, and children (Schneider et al 2009;Gonzales et al 2012).…”
Section: Introductionmentioning
confidence: 99%